Embodiment and the Unseen - Ida Albertina Tevajärvi 1996- (2022)
This dissertation reflects on the experience of the unseen, the transcendent, the nonconceptual, and the embodied, seen from the perspective of performative, inter-disciplinary art practices, and suggests that these could help bridge gaps between human and non-human, needed to achieve planetary equilibrium. The text uses traditional Finnish and Karelian thought, depicting a relationship to the world, spaces, the non-human, the human as agency filled, soulful and interconnected. The thinking of old is paired with current feminist phenomenological and post humanism, with Astrida Neimani’s and Irigaray’s philosophy, as well as Rosi Braidotti’s and Karen Barad’s. Notions of fluidity between the inner and the outer is considered with studies of the nature of transcendence using Jonna Bornemark’s furthering on Max Scheler’s and Husserl’s phenomenology. The soulful and ritual is suggested as unseen rooms or membranes within the physical space, accessible, and sources for knowledge worth cultivating in a western society. Light is also shed on how the femininely coded (the visionary, the sensory, the bodily, the personal), cannot be understood if restrained by a ‘phallogocentric logic’ (Irigaray’s term). Through examining female archetypical characters of the Finnish Karelian epos Kalevala the ability of transformation is discussed. Female mystics and oral traditions as well as the mythical and early understandings of words and their relationships to the world and its unseen aspects are meditated upon, from Juha Hurme’s book Niemi. Possible consequences of a lack of words and knowledge about the nonconceptual (using Tibetan Buddhist terminology) as well as the femininely coded qualities are discussed, suggesting artistic practice as an important tool or antidote in shifting awareness and narrative. The ritual is looked upon with Randal Collin’s eyes, both assessing its artistic properties as well as applying it to the world of academia and intellectuals, considering idea and text as sacred objects of today.